Effect of thermal collective modes on the Stark broadening of hydrogen spectral lines in strongly coupled plasmas. (23rd February 2016) - Oks, E
Abstract: The paper is motivated by the recent (2014) benchmark measurements of the full width at half maximum (FWHM) of the H α line by Kielkopf and Allard (KA), which reached the electron densities N e by two orders of magnitude greater than the corresponding previous benchmark experiments, namely up to N e = 1.4 × 10 20 cm −3 . At this range of N e, no theoretical calculations of the FWHM of the H α line existed, except calculations by KA; however, the latter is inconsistent because of the neglect of the contribution by plasma electrons. In the present paper we develop a consistent analytical theory that is relevant to the range of the electron densities reached in KA experiment. At this range of N e, a new factor becomes significant—the factor never taken into account in any previous simulations or analytical theories of the Stark broadening of hydrogen spectral lines: a rising contribution of the electrostatic plasma turbulence (EPT) at the thermal level of its energy density. We show that this contribution becomes comparable to the corresponding contribution by electron and ion microfields at this range of N e . As a result, our theoretical FWHM of the H α line becomes in a very good agreement with the experimental FWHM of the H α line by KA in the entire range of their electron densities. The present theory can be also used for calculating Stark profiles and the FWHM of other hydrogen spectral lines.